2014
DOI: 10.1111/jofo.12056
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behavior of migrant warblers in mixed-species flocks in Venezuelan shade coffee: interspecific differences, tree species selection, and effects of drought

Abstract: ABSTRACT. Shade coffee has been identified as an important habitat for Nearctic-Neotropical migrants during the non-breeding season, including species of conservation concern such as Cerulean Warblers (Setophaga cerulea). To better understand habitat features important for migrants in shade coffee, we studied the foraging behavior of migrants in mixed-species flocks at six shade-coffee farms in the Cordillera de Merida, Venezuela, in 2008Venezuela, in -2009 and the El Niño drought year of 2009-2010. We exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…Three sites had recently been partially harvested to ∼50% stocking (Newell and Rodewald , ). During the non‐breeding season, we studied Cerulean Warblers at six shade coffee farms on the western slopes of the Cordillera de Merida in the Venezuelan Andes (Bakermans et al , , Newell et al ). Field work was conducted for seven weeks from 27 November 2008 to 28 January 2009 during a non‐drought year.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three sites had recently been partially harvested to ∼50% stocking (Newell and Rodewald , ). During the non‐breeding season, we studied Cerulean Warblers at six shade coffee farms on the western slopes of the Cordillera de Merida in the Venezuelan Andes (Bakermans et al , , Newell et al ). Field work was conducted for seven weeks from 27 November 2008 to 28 January 2009 during a non‐drought year.…”
Section: Methodsmentioning
confidence: 99%
“…We observed foraging behavior from 27 April through 9 July at six sites in two state forests in Vinton and Jackson counties. Three sites had recently been partially harvested to ß50% stocking Rodewald 2011, 2012). During the non-breeding season, we studied Cerulean Warblers at six shade coffee J.…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a precise definition of nuclear species and their We observed that several migratory species such as Piranga rubra, Leiothlypis peregrina, Setophaga petechia, S. fusca, Geothlypis philadelphia, Cardellina canadensis, and M. varia joined MBF at Quindío, being some of them common or identified as potential nuclear species. Migratory species participate frequently in MBF in the tropical Andes, but those studies had been focused mainly in agroforestry ecosystems or secondary forests (Arbeláez-Cortés, Rodríguez-Correa et al 2011;McDermott & Rodewald 2014;Newell et al 2014). Here we document these migratory species in several forest fragments indicating that they do not only join MBF in different habitats, but also could have a role in their cohesion.…”
Section: Studies On Neotropical Fauna and Environment 11mentioning
confidence: 99%
“…In many traditional studies on resource partitioning, researchers consider how environmental heterogeneity can enable species to differentially access resources. Species can feed in different habitats and microhabitats (Navarro et al 2009;Symes et al 2013;, on different items (Pulliam 1985;Beaulieu and Sockman 2012), at different times (Chesson 2000;Reum & Essington 2008), and by using different foraging methods (Toft 1980;Frere et al 2008;Knickle and Rose 2014;Newell et al 2014;O'Neill and Gibb 2014). While many of these studies demonstrate niche partitioning, they do not consider the role that individual and/or ontogenic trait variation may play in niche partitioning (Hirai andMatsui 2002, Lasky et al 2014).…”
Section: Introductionmentioning
confidence: 99%